Medical Aspects for Risk Factors of Acute Otitis Media in Early Age Kids of Play Group, A Clinical Study - Munir Ahmad Baloch, Muhammad Amir, Zaheer Hussain Memon, Naveed Shuja, Arslan Shuja, Asfand Yar Mujahid (Pakistan Journal of Medical & Health Sciences, 2022)
Task: The diagnosis of acute otitis media is very common in young children. Its chronic condition may cause hearing impairment and delayed speech in young children. Aims and Objectives: The aims and objectives of current study were to provide health awareness against risk factors of acute otitis media in our community. Methodology: In this study total 200 children of age 1-3 years old were selected and divided them into two groups. In Group-A 100 children were with the symptoms of acute otitis media while in Group-B 100 children were those how have not acute otitis media. The study was conducted in ENT department of different medical institutes. The time duration of study was 6 month. Results: In this study the percentage standard mean deviation of non-biological variables in table-2, for Group-A, household firewood (12.8±0.2), cigarette smoke (42.4±0.1), economic conditions (32.6±0.2), lack of medical awareness (41.1±0.1), family history (6.09±0.1), malnutrition (21.03±0.3) and Group-B, household firewood (1.08±0.1), cigarette smoke (12.1±0.1), economic conditions (2.3±0.2), lack of medical awareness (51.1±0.1), family history (4.01±0.1) and malnutrition (1.01±0.3) were respectively. While the percentage standard mean deviation of biological risk factors in table-3 for Group-A, S. pneumonia (10.2±0.1), H. influenza (12.01±0.2), Moraxella catarrhalis (9.04±0.1) and Group-B S. pneumonia (01.0±0.1), H. influenza (1.01±0.2), Moraxella catarrhalis (1.01±0.3) were measured. Conclusion: It was concluded that household firewood, cigarette smoke, economic conditions, lack of medical awareness, family history and malnutrition were the major associated factors occurrence of acute otitis media in children. It is so important to provide health awareness against these factors in community.